CFD simulation of bubbly two-phase flow in horizontal pipes - Mohd Saidi, Wan Ahmad (2009)
Modeling of two phase flow, particularly liquid-vapor flow under diabatic conditions inside a horizontal pipe using CFD simulation is difficult with the available two phase models in FLUENT due to continuously changing flow patterns. In the present analysis, CFD analysis of air-water bubbly two-phase flow inside a horizontal pipe of inner diameter, 38.1 mm and 2000 mm length has been modeled using the volume averaged multiphase flow equations. Liquid volumetric superficial velocities varied at constant 1.56 m/s and gas volumetric superficial velocities varied in the range from 0.15 to 0.8 m/s. The average gas volume fraction varied in the range from 4% to 16%. The predicted gas volume fraction and mean gas velocity are compared with the experimental data that has been run before. The model prediction shows better agreement with experimental data is obtained using k-ε model with constant bubble size (1 mm). The results indicate that the volume fraction has a maximum near the upper pipe wall, and the internal flow structure is varies with increasing superficial gas velocity. It was found that increasing the superficial gas velocity at fixed superficial liquid velocity would increase the local gas volume fraction. The simulation results were consistent with experimental observations. An interesting feature of the liquid velocity distribution is that it tends to form a fully developed turbulent pipe flow profile at the lower part of the pipe, whereas in the top of the pipe a different flow exists.-Author-